Tenacibaculosis caused by Tenacibaculum maritimum: Updated knowledge of this marine bacterial fish pathogen - Mabrok, Mahmoud; Algammal, Abdelazeem M.; Sivaramasamy, Elayaraja; Hetta, Helal F.; Atwah, Banan; Alghamdi, Saad; Fawzy, Aml; Avendaño-Herrera, Ruben; Rodkhum, Channarong (Frontiers in Cellular and Infection Microbiology, 2023)
Tenacibaculosis occurs due to the marine bacterial pathogen Tenacibaculum maritimum. This ulcerative disease causes high mortalities for various marine fish species worldwide. Several external clinical signs can arise, including mouth erosion, epidermal ulcers, fin necrosis, and tail rot. Research in the last 15 years has advanced knowledge on the traits and pathogenesis mechanisms of T. maritimum. Consequently, significant progress has been made in defining the complex host-pathogen relationship. Nevertheless, tenacibaculosis pathogenesis is not yet fully understood. Continued research is urgently needed, as demonstrated by recent reports on the re-emerging nature of tenacibaculosis in salmon farms globally. Current sanitary conditions compromise the development of effective alternatives to antibiotics, in addition to hindering potential preventive measures against tenacibaculosis. The present review compiles knowledge of T. maritimum reported after the 2006 review by Avendaño-Herrera and colleagues. Essential aspects are emphasized, including antigenic and genomic characterizations and molecular diagnostic procedures. Further summarized are the epidemiological foundations of the T. maritimum population structure and elucidations as to the virulence mechanisms of pathogenic isolates, as found using biological, microbiological, and genomic techniques. This comprehensive source of reference will undoubtable serve in tenacibaculosis prevention and control within the marine fish farming industry. Lastly, knowledge gaps and valuable research areas are indicated as potential guidance for future studies.